Portuguese knowledge intensive business services: What do we know about them? - Luísa Carvalho; Sandra Pinto (Tourism & Management Studies)
In Europe, most of the earlier studies applied to KIBS (knowledge intensive business services) were developed in North European countries (Finland, Sweden, Norway, UK or German) where that research is already consistent and widespread. However, the study of KIBS is in its infancy in other European countries. In this article we demonstrate that research into Portuguese KIBS is still very recent and incipient. We also aim to contribute to the discussion of the significance of KIBS to Portuguese economy where the weight of services sector is preponderant. We present a literature review showing how the KIBS have evolved in Portugal by drawing portraits of two decades. We complement this with an empirical study using the Community Innovation Survey (CIS) 2008. We emphasize that there is still much to learn about Portuguese KIBS.